2007
DOI: 10.1002/ajh.21074
|View full text |Cite
|
Sign up to set email alerts
|

Utility of consecutive repeat HIT ELISA testing for heparin‐induced thrombocytopenia

Abstract: Heparin‐induced thrombocytopenia (HIT) is a serious complication of heparin therapy. Limited data are available regarding repeat HIT antibody testing after an initial negative test. We conducted a retrospective study to determine the utility of repeat testing. Heparin antibodies were detected using the GTI‐PF4 enzyme‐linked immunoabsorbent assay, ELISA (GTI Diagnostics, Waukesha, WI). Patients (n = 137) were assigned to one of three groups based upon the initial negative test optical density (OD) range of low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…As shown in our study, there is limited accord between H-PF4 ELISA screening results and confirmed HIT cases for patients on ECLS (3). Furthermore, HIT may still be present in patients on ECLS despite negative testing (5,33). According to our analysis, the SRA was positive only in 32% of clinically confirmed HIT, which may indicate that the test may not be specific enough.…”
Section: Ecmomentioning
confidence: 65%
“…As shown in our study, there is limited accord between H-PF4 ELISA screening results and confirmed HIT cases for patients on ECLS (3). Furthermore, HIT may still be present in patients on ECLS despite negative testing (5,33). According to our analysis, the SRA was positive only in 32% of clinically confirmed HIT, which may indicate that the test may not be specific enough.…”
Section: Ecmomentioning
confidence: 65%
“…One retrospective analysis reported that an initially negative PF4 test converting to a positive result was associated with thrombosis only if the 4T score increased in a concurrent fashion. 20 Also, ELISA optical density values for PF4 antibodies were not reported during this time frame, and these data may help predict thrombotic risk in isolated cases of HIT. 21 Finally, because it was not locally available, the serotonin release assay (a potentially confirmatory laboratory test) was not performed.…”
Section: Limitationsmentioning
confidence: 88%
“…41 However, when the suspicion of HIT is high based on clinical symptoms one negative test should not rule out HIT, as a subsequent test is often positive. 82,83 There are also frequent reports of platelet-activating antibodies being present in HIT ELISAnegative specimens. 32,34,59,72,83 The interpretation and value of HIT-diagnostic tests vary with timing of collection of the patient specimen, as well as with the clinical status of the patient.…”
Section: Interpretation Of Assay Resultsmentioning
confidence: 99%